THE IMPLEMENTATION OF DIRECTED READING THINKING ACTIVITY (DRTA) IN LITERACY-BASED LANGUAGE TEACHING AT LEMBAGA BIMBINGAN BELAJAR TELADAN KUDUS - Diah Kurniati Tafsir; Suprihadi Suprihadi (Prominent, 2019)
For most foreign language learners, understanding texts written in a foreign language is not an easy thing to do. To help learners in coping with this problem, when teaching reading teachers should provide them with a number of structured tasks that not only focus on students’ reading purpose, but also allow them to confront and reflect upon reading difficulties in socially interactive ways and one of the activities which is appropriate with these tasks is Directed Reading Activity (DRTA). The objective of the research is to compare the behavior of the English reading class students before and after the implementation of DRTA. The subjects of this research were 3 students of LBB Teladan Kudus. The conclusion is that the behavior of the students is better than that before the implementation of DRTA. The students become motivated, active, enthusiastic, paid attention to the teaching learning process, and got involved in the teaching learning process. Considering that DRTA has many benefits for learners especially dealing with learners’ behaviors, it is suggested that this activity should be used by the teacher when teaching reading.